Creating Spaces of Engagement: Exploring High School Youth's Voices in Reshaping the Social Justice Curriculum - Shuyuan Liu; Kenneth Gyamerah; Claire Ahn; Thashika Pillay (University of Windsor, 2024)
The current structure of formal education makes it difficult for teachers and students to hold meaningful conversations to support high-school youth's meaning-making of critical social-justice issues. This paper presents data on three high-school youth's knowledge and experiences with social justice issues during the pandemic. Specifically, the paper aims to explore how youth construct knowledge and counter dominant discourses through utilizing informal learning spaces, such as social media platforms, peer and family conversations, as well as personal encounters. In addition, and more importantly, an exploration of how formal education can incorporate social-justice issues into the curriculum is considered. The analysis of these high school youth's interview conversations presents their diverging needs to learn about social-justice topics in both formal and informal learning contexts. The data also illustrates the power of their voices in a way that could inform future curriculum development. Discussions and implications highlight the possibility of creating such ethical spaces in formal education to engage in social-justice topics.